Functional characterization on native starch of Peruvian native potatoes (Solanum phureja) - Martínez, P. (2015)
There are many varieties of native potatoes grown in different regions of Peru, usually for farmers´ consumption. However, the possibility of a commercial use has led this work in order to give them added value. To evaluate the possibility of use of native starch from these potatoes, as an ingredient in the food industry, it was presented as objective to determine the physicochemical, functional and viscoelastic native potato starches obtained from Pampacorral properties (Cuzco, Peru): Puka Ambrosio (PA), Combe (CO), Perwanita (PER), Kalis qero (KQ), Qello virondos (QEV), Yana churos (YACH), Pitikiña (PI), Yana kusi (YAKU) y Solischa (SOL). For this purpose, slurries were prepared from native starch by heating until gelatinization. Moisture sorption, swelling and solubility showed were correlated with temperature increment. At 90 °C, PI starch showed greater values for swelling power (28.47%), water binding capacity index (22.70) and solubility (20.24%). Syneresis values, at 4 °C, were the lowest for CO and YACH starches, 3.8 and 4.6; respectively. All native potato starch gels showed pseudoplastic behavior (n G”) for varieties tested.